2020
DOI: 10.1192/bjo.2019.101
|View full text |Cite
|
Sign up to set email alerts
|

Carers' experiences of involuntary admission under mental health legislation: systematic review and qualitative meta-synthesis

Abstract: Background Carers are key providers of care and support to mental health patients and mental health policies consistently mandate carer involvement. Understanding carers' experiences of and views about assessment for involuntary admission and subsequent detention is crucial to efforts to improve policy and practice. Aims We aimed to synthesise qualitative evidence of carers' experiences of the assessment and detention of their family and friends under mental health legislation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(56 citation statements)
references
References 49 publications
9
47
0
Order By: Relevance
“…Indeed, cooperation with professionals was seen as challenging, especially if they had different views of the patient’s needs in inpatient care. As found in earlier studies [ 66 , 67 ], caregivers had contradictory feelings when a person with SSD was admitted to a hospital. They were relieved that the person was getting help; however, they also felt that they did not receive information and that they were ignored as a resource in care.…”
Section: Discussionmentioning
confidence: 64%
“…Indeed, cooperation with professionals was seen as challenging, especially if they had different views of the patient’s needs in inpatient care. As found in earlier studies [ 66 , 67 ], caregivers had contradictory feelings when a person with SSD was admitted to a hospital. They were relieved that the person was getting help; however, they also felt that they did not receive information and that they were ignored as a resource in care.…”
Section: Discussionmentioning
confidence: 64%
“…In contrast, convincing the patient sometimes proved difficult, and psychiatrists tried to provide guidance and balanced information during these trying times [ 20 ]. Their goal was to avoid the entanglement of care and coercion which affects caregivers, the patients and their families [ 21 , 22 ]. Their feeling of exigency to implement organicity investigations may also originate from the relatively high frequency of psychoses of organic origin in the expert centers they trained at.…”
Section: Discussionmentioning
confidence: 99%
“…Involuntary psychiatric admissions go against the fundamental health care principle of patient autonomy (1,2). Many individuals exposed to such admissions, along with their carers, report experiences of fear and distress (3,4). Moreover, evidence that coercive practices lead to better outcomes is limited (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…Although services at the primary health care level play a key role in providing services to people with severe mental illness (SMI), the role of these services in such paths remains largely undocumented (13,14). Persons with lived experience of involuntary admission have reported lack of information and involvement in treatment decisions (3); carers experience difficulties getting preventive help prior to an individual's acute crisis and report lack of adequate support for themselves in such situations (4). A systematic review and meta-synthesis of multiple stakeholders' experiences with involuntary psychiatric admission decision-making found that collaboration between the services involved was lacking, that medical views dominated assessments, and that the admission process could be experienced as heavy-handed (especially given that it often involves police) (15).…”
Section: Introductionmentioning
confidence: 99%